A new model of clientelism: political parties, public resources, and private contributors. Issue 1 (18th September 2015) - Gherghina, Sergiu; Volintiru, Clara
Abstract : The study of clientelism has pointed in the direction of a pyramid structure in which selective benefits are distributed with the help of brokers to individuals or groups in exchange for political support. This approach treats the resources aimed to enhance electoral mobilization as endogenous and fails to explain what happens when brokers have very low capacity. To address these problems this article proposes a bi-dimensional model of clientelism that emphasizes the role of exogenous resources. Accordingly, the vertical linkage between political parties and the electorate is complemented by a horizontal nexus between parties and private contributors. In an environment characterized by low internal resources, parties involve external actors to get the necessary money. To illustrate how this mechanism works we focus on Romania between 2008 and 2012, a crucial case for the study of clientelism.